THE DEVELOPMENT TREND OF ARTIFICIAL INTELLIGENCE (Modern education and development, 2025)
This article analyzes the development trends of artificial intelligence technologies. It discusses the development of artificial intelligence in learning and decision-making, natural language processing, automated systems and robotics, and the impact of high-level automation and the workforce. The article analyzes the current and future trends of artificial intelligence, its opportunities and risks, as well as its role in society.